Multilevel Continuous Polarization Modulation With High Spectral Efficiency in the Depolarization Channels - Fangfang Liu (IEEE Access, 2018)
Facing the challenges of spectrum shortage and complex depolarization effects in wireless communication, a multilevel continuous polarization modulation (MCPoM) scheme is investigated to achieve high spectral efficiency and improve the symbol error rate performance in the practical depolarization channels. The principle of the MCPoM modulation is stated in details on the basis of the MCPoM system model. Then a noncoherent and a coherent MCPoM demodulation methods are proposed as the differential demodulation and the suboptimum sequence detection based demodulation, respectively. Furthermore, considering the depolarization effect of polarization-dependent loss in the practical wireless channels, MCPoM is evaluated with two influences of power attenuation and polarization difference distortion. After that, we propose a polarization pre-compensation algorithm for MCPoM to mitigate the influences of polarization-dependent loss. The performances of the proposed scheme are evaluated with symbol error rate and spectral efficiency. Simulations results demonstrate that higher spectral efficiency and enhanced symbol error rate of the proposed MCPoM scheme are guaranteed in the depolarization channels.